The assembly of RAB22A/TMEM33/RTN4 initiates a secretory ER-phagy pathway - Xueping Zheng; Dongmei Fang; Hao Shan; Beibei Xiao; Denghui Wei; Yingyi Ouyang; Lanqing Huo; Zhonghan Zhang; Yuanzhong Wu; Ruhua Zhang; Tiebang Kang; Ying Gao (Cell Discovery)
Abstract Rafeesome, a newly identified multivesicular body (MVB)-like organelle, forms through the fusion of RAB22A-mediated ER-derived noncanonical autophagosomes with RAB22A-positive early endosomes. However, the mechanism underlying the formation of RAB22A-mediated noncanonical autophagosomes remains unclear. Herein, we report a secretory ER-phagy pathway in which the assembly of RAB22A/TMEM33/RTN4 induces the clustering of high-molecular-weight RTN4 oligomers, leading to ER membrane remodeling. This remodeling drives the biogenesis of ER-derived RTN4-positive noncanonical autophagosomes, which are ultimately secreted as TMEM33-marked RAB22A-induced extracellular vesicles (R-EVs) via Rafeesome. Specifically, RAB22A interacts with the tubular ER membrane protein TMEM33, which binds to the TM2 domain of the ER-shaping protein RTN4, promoting RTN4 homo-oligomerization and thereby generating RTN4-enriched microdomains. Consequently, the RTN4 microdomains may induce high curvature of the ER, facilitating the bud scission of RTN4-positive vesicles. These vesicles are transported by ATG9A and develop into isolation membranes (IMs), which are then anchored by LC3-II, a process catalyzed by the ATG12-ATG5-ATG16L1 complex, allowing them to grow into sealed RTN4 noncanonical autophagosome. While being packaged into these ER-derived intermediate compartments, ER cargoes bypass lysosomal degradation and are directed to secretory autophagy via the Rafeesome-R-EV route. Our findings reveal a secretory ER-phagy pathway initiated by the assembly of RAB22A/TMEM33/RTN4, providing new insights into the connection between ER-phagy and extracellular vesicles.